2019
DOI: 10.1021/acs.langmuir.8b03879
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Intercalant Assemblies at the Graphene–Metal Interface

Abstract: The influence of graphene on the assembly of intercalated material is studied using low-temperature scanning tunneling microscopy. Intercalation of Pt under monolayer graphene on Pt(111) induces a substrate reconstruction that is qualitatively different from the lattice rearrangement induced by metal deposition on Pt(111) and, specifically, the homoepitaxy of Pt. Alkali metals Cs and Li are used as intercalants for monolayer and bilayer graphene on Ru(0001). Atomically resolved topographic data reveal that at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 121 publications
(274 reference statements)
0
2
0
Order By: Relevance
“…[ 13 ]). However, there is rather scarce evidence of graphene-induced reconstruction in systems where graphene, weakly interacting with monolayers or sub-monolayers of metals, induced their reconstruction [ 34 , 35 ]. As reported by Jolie et al [ 34 ], Ag-intercalating graphene flakes on Ir(111) exhibit a complicated aperiodic structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 13 ]). However, there is rather scarce evidence of graphene-induced reconstruction in systems where graphene, weakly interacting with monolayers or sub-monolayers of metals, induced their reconstruction [ 34 , 35 ]. As reported by Jolie et al [ 34 ], Ag-intercalating graphene flakes on Ir(111) exhibit a complicated aperiodic structure.…”
Section: Resultsmentioning
confidence: 99%
“…It appears that the emergence of multiple rotational domains, combined with a strong dependence on the local strain, is responsible for the absence of the short-range pattern order. The Gr/Pt/Pt(111) system, studied by Halle et al [ 35 ], showed a modification to the Pt(111) reconstruction upon the intercalation of Pt. The modification was ascribed to the change in the adsorption energy landscape for Pt on Pt(111).…”
Section: Resultsmentioning
confidence: 99%